WORK WITH TEXT IN NATIVE LANGUAGE LESSONS (Web of Teachers: Inderscience Research, 2024)
This article explores the effectiveness of text-based methods in native language lessons. It explores how language proficiency can be improved by including different types of text such as literary works, articles, and actual materials. The study explores literature, methodologies, outcomes, and outcomes to provide insight into the optimization of native language learning.